Effects of taxifolin from enzymatic hydrolysis of Rhododendron mucrotulatum on hair growth promotion - Park, Sun-Min; He, Yi-Chang; Gong, Chun; Gao, Wei; Bae, Young-Soo; Si, Chuanling; Park, Kwang-Hyun; Choi, Sun-Eun (Frontiers in Bioengineering and Biotechnology, 2022)
In general, compared to glycosides, flavonoid aglycones have stronger bioactivities, such as antioxidant and antidiabetic activities. But taxifolin, a flavonoid aglycones, is detected only in trace amounts in nature and is not easily observed. However, in this study, to investigate the hair tonic and hair loss inhibitors effect of taxifolin, high content of taxifolin aglycone extract was prepared by enzymatic hydrolysis. Taxifolin effectively regulates the apoptosis of dermal papilla cells, which is associated with hair loss, based on its strong antioxidant activities. However, inhibition of dihydrotestosterone (DHT), which is a major cause of male pattern hair loss, was significantly reduced with taxifolin treatment compared with minoxidil, as a positive control. It was also confirmed that a representative factor for promoting hair growth, IGF-1, was significantly increased, and that TGF-β1, a representative biomarker for hair loss, was significantly reduced with taxifolin treatment. These results suggest that taxifolin from enzymatic hydrolysis of RM is a potential treatment for hair loss and a hair growth enhancer.